Exploitation of diversity within farmers' durum wheat varieties enhanced the chance of selecting productive, stable and adaptable new varieties to the local climatic conditions - Mengistu, D.K.; Kiros, A.; Mohammed, J.; Tsehaye, Y.; Fadda, Carlo (Cambridge University Press, 2019)
Variety selection from locally adapted crops is the major climate change adaptation strategy of farming communities. There are several justifications for re-thinking for the sustainable use of crop biodiversity in our breeding programs. Thirty-one durum wheat farmers' varieties (FVs), together with five improved check varieties, were characterized in Tigray during 2014 and 2015 main cropping seasons. The genotype effect explained most of the variations in measured traits, which enabled us to identify superior and stable genotypes for wider adaptation as well varieties with more local adaptation. The genotypes and test locations imposed a highly significant (P < 0.001) effect on both phenological and quantitative traits. A yield advantage of 14.3% was obtained from top performer FV over top performer improved variety, Asassa. Of the tested FVs, 27.8% were superior for grain yield (GY) than improved varieties and 19.4% of these superior FVs were more stable and adaptable than the improved varieties. Besides giving higher GY with spatial stability, they qualify for industrial requirements with high-grain protein (>13%) and gluten (>33%) contents. FVs such as G10, G16, G21, G22 and G30 have wider adaptability and are suitable for production in all tested areas. As outcome of this study, two superior FVs, G10 (208304) and G30 (8208), were nationally released for commercial production for their productivity, stability and grain quality. Utilizing the diverse durum wheat FVs can effectively improve productivity and adaptability. Wheat breeders need to revisit these resources to improve adaptation of wheat production to the changing climatic conditions.